PEMBANGUNAN HUKUM: PERAN HUKUM DALAM MENINGKATKAN LITERASI KEUANGAN INKLUSIF PADA PINJAMAN ONLINE - Nurhilmiyah, Nurhilmiyah; Kalsum, Ummi (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
Law has the power to improve the national economy and public welfare through public behavior. Oneof the methods is increasing financial literacy on online loans in the context of economic developmentlaw. There have been many legal cases related to peer-to-peer lending (P2PL) since its proliferation inIndonesia. For example, many parties impose interest rates that exceed the upper limit set by thestrategic partner of the Financial Services Authority (OJK, Otoritas Jasa Keuangan), the IndonesianFintech Joint Funding Association (APFI, Asosiasi Pendanaan Bersama Fintech Indonesia). Inaddition, there is minimal public knowledge regarding their rights and obligations towards creditorsor investors, loan service providers, information technology-based money lending services, and otherdebtors or online loan customers. These examples emphasize the importance of studies regarding thistopic. This study aims to elaborate on the role of law in increasing inclusive financial literacy on onlineloans in the context of economic development law.